The interaction of nitrogen and potassium nutrients in increasing growth, yield, and quality of sweet corn products - Syarifah, Risqa Naila Khusna; Purwanto, Purwanto; Sarjito, Agus; Hanifa, Hana; Bayyinah, Lafi Na'imatul (Kultivasi, 2025)
Fertilizer application is a strategy that can be used to increase sweet corn production and maintain environmental balance. This research aims (i) to determine the optimal dose of nitrogen and potassium fertilizers for sweet corn production; (ii) to study the agronomic and physiological responses of sweet corn plants at different nitrogen and potassium dose; and (iii) to determine the nitrogen (N) and potassium (K) nutrient uptake and efficiency by sweet corn at different fertilizer doses and their interactions on yield and yield quality. The research was conducted from March to November 2022 in the Faculty of Agriculture, Universitas Jenderal Soedirman. The experimental design used was a randomized block design. The treatments tried were N doses (0 kg ha-1 (N0), 100 kg ha-1 (N1), 200 kg ha-1 (N2)) and K doses (0 kg ha-1 (K0), 75 kg ha-1 (K1), 150 kg ha-1 (K3)). Each treatment was repeated three times. The observational data were analyzed using analysis of variance to determine the effect of treatment. If the results differed significantly, Duncan’s multiple range test (α=5%) was performed. Variables observed included growth traits, yield and yield components, physiological, biochemical, nutrient uptake and efficiency, and sweetness level. The experimental results showed that nitrogen dosage had a significant influence on growth traits, yield, and yield components, physiological, biochemical, nutrient uptake and efficiency, and sweetness level. The K dosage had a significant influence on N and K nutrient uptake. The interaction between a N dose of 100 kg ha-1 and a K dose of 150 kg ha-1 shows the best values for plant growth rate and potassium uptake.